Modulation of magnetic properties at room temperature: coordination-induced valence tautomerism in a cobalt dioxolene complex. - Witt, Alexander; Heinemann, Frank Wilhelm; Sproules, Stephen; Khusniyarov, Marat (Chemistry - A European Journal, 2014)
The valence-tautomeric six-coordinate complex [Co(tbdiox)2(4-papy)2] (1; tbdiox = redox-active 3,5-di-tert-butyl-o-dioxolene, 4-papy = 4-phenylazopyridine) was synthesized and its electronic structure examined. Whereas 1 shows regular thermally driven valence tautomerism in the solid state, it partially dissociates in solution to form the five-coordinate species [Co(tbdiox)2(4-papy)] (2) and free 4-papy. Species 1 and 2 exhibit different electronic structures-low-spin (ls) Co(III) and high-spin (hs) Co(II), respectively-in solution at room temperature and therefore different magnetic properties. Since 1 and 2 are in an equilibrium that is 4-papy-dependent, the magnetic moment of the solution species can be tuned by means of the ligand content. Thus, the concept of coordination-induced valence tautomerism (CIVT) has been introduced. The electronic structures of 1 and 2 as well as their CIVT were elucidated by X-ray crystallography, electrochemistry, titration experiments, and all variable-temperature SQUID susceptometry, NMR, EPR, and electronic absorption spectroscopy. The experimental findings are strongly supported by broken-symmetry DFT calculations. The magnetic exchange interactions in different types of valence-tautomeric cobalt complexes were explored computationally.